Abordagem das capacidades como meio para mensuração da criação de valor social na ação dos empreendimentos sociais - Braga, Clara Suzana Cardoso (2020)
Considering the role of Social Entrepreneurship in the search for minimizing social issues, the relevance of efficient means for measuring their social results, especially the creation of social value, is understood as changes in people's well-being. Amartya Sen provides a multidimensional perspective of the concept of well-being, not limited to economic development alone, since, according to his assumptions, the capability approach operates at two levels: at the level of well-being achieved, which is measured by functionings (achievements/effectuation), and the level of potential or viable well-being, which is measured by capabilities (set of achievements/ effectuation). This research aims to propose a tool to measure Creation of Social Value by Social Entrepreneurship, based on Sen's Capabilities Approach. In order to meet the research objective, a survey was carried out with a sample of 214 beneficiaries of 4 Social Enterprises: i) homeless adults in the city of Fortaleza; ii) young people living in rural areas of the state of Ceará; iii) children and adolescents in a context of social vulnerability and iv) women in a context of social vulnerability. Amartya Sen's capability approach was used, through applying the assessment tool by Anand et al. (2011), to measure the level of well-being of beneficiaries of Social Enterprises. The results indicate that the research tool translated into Portuguese, based on factor analysis, had a new model suggested, with the exclusion of 11 variables and being remodeled from the 10 constructs in the model by Anand et al (2011) to 4 constructs: [1] Affiliation; [2] Control over the environment; [3] Physical and Emotional Security and [4] Work. It was also found that the higher the values related to personality traits Extroversion and Positive Past Experiences, the greater the respondents' perception of well-being and, on the other hand, the higher the values related to personality traits Emotional Stability, the lower the respondents' perception of well-being. The average tests indicated the research tool's sensitivity to the perception of capabilities and well-being between different socioeconomic groups, differences based on the literature about discrimination and violence experienced by people in a context of homelessness; studies on the civil rights of children and adolescents and studies on gender violence.